Investigate the Root Determinants of Examiner Performance - Ikhwan Wicaksono; Indarto Indarto; Aprih Santoso (Universitas Muhammadiyah Sorong, 2023)
The purpose of the study was to analyze and empirically prove the effect of work stress, workload, work discipline on the examiner's performance with work motivation as a mediating variable at the Central Java Provincial BPK Representative. This type of research is Explanatory Research, which is to clarify the relationship between research variables and test hypotheses that have been formulated with a quantitative approach. The research method used is a survey method. The population in this study were all employees of the Central Java Provincial BPK who served in the Examination Section totaling 140 people. Calculation of the sample using the Slovin formula: the number of samples in this study was 104 people. In this study the research variables, namely: Independent variables: work stress, workload, work discipline and the mediating variable: work motivation and the dependent variable: employee performance. The data analysis techniques used are: Descriptive analysis, Validity Test, Reliability Test, Normality Test Classical Assumption Test (Multicolonierity Test, Heteroscedasticity Test), Two-Stage Multiple Regression Analysis, t Test, Mediation Test, Coefficient of Determination (R Square). The results showed that job stress. work discipline and work motivation significantly influence the examiner's performance. Work stress and work discipline have a significant effect on work motivation. Workload has no significant effect on work motivation. Work Motivation mediates work stress and work discipline on examiner's performance. Work motivation cannot mediate Workload on Examiner's Performance.